2018
DOI: 10.3912/ojin.vol23no03man02
|View full text |Cite
|
Sign up to set email alerts
|

Child Poverty, Toxic Stress, and Social Determinants of Health: Screening and Care Coordination

Abstract: Social determinants of health (SDOH) refer to the social, economic, and physical conditions in which people live that may affect their health. Poverty, which affects nearly 15 million children in the United States, has far-reaching effects on children’s physical and mental health. Although it is difficult to change a family’s economic circumstances, nurses can play a critical role to address SDOH through screening and effective coordination of care. As nurses, our role is to minimize the effects of SDOH, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…Participants clicked a box next to any domain for which they wanted to receive assistance. These domains were selected because deficits in these areas have been associated with stress and negative impacts on individuals and their families in the short and long term [ 43 ]. Local community resources were identified through various methods.…”
Section: Methodsmentioning
confidence: 99%
“…Participants clicked a box next to any domain for which they wanted to receive assistance. These domains were selected because deficits in these areas have been associated with stress and negative impacts on individuals and their families in the short and long term [ 43 ]. Local community resources were identified through various methods.…”
Section: Methodsmentioning
confidence: 99%
“…This may include drawing from a variety of creative and reflective teaching methods in the literature to create transformative learning opportunities while engaging all students in SDH content regardless of their starting place. [33][34][35][36] Finally, preclinical curricular reform should elevate the voices of both students and faculty identifying as women and BIPOC, as these individuals are more likely to have felt the effects of social forces on health and well-being.…”
Section: Next Steps and Recommendationsmentioning
confidence: 99%
“…Interesting concentrations of high ACT scores have been found in several vulnerable populations, such as those living in poverty (Francis et al, 2018); individuals who were the victims of human trafficking (Reid et al, 2017), women of color (Corbin et al, 2013), Persons of First Nations (Nurius et al, 2016), individuals who identify as members of the LGBTQ+ community (Blosnich & Anderson, 2015), those struggling with substance use disorders (Fuller- Thomson et al, 2016), and female sex offenders (Willis & Levenson, 2016). Thomas and Jaque (2018) investigated childhood adversity in professional performing artists, and found that increased reports of childhood abuse and neglect by actors.…”
Section: Adverse Childhood Experience (Ace) and Childhood Toxic Stressmentioning
confidence: 99%
“…Due to personal experiences, perceptions of traumatic events, personality factors, temperaments, and several other nuances, no two people experience trauma in the same manner. It is also difficult to separate the effects of trauma and poverty on future outcomes (Francis et al, 2018).Therefore, it is difficult to separate the effects of trauma, personal factors, lower socioeconomic status, and resulting outcomes. Additionally, the overall sample is small (n = 95), making the results of this study primary.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation